Standardising Early Career Talent Management in Multinational Corporations on the Example of Edwards Lifesciences : Challenges, Success Factors and Success Metrics - Feil, Lea; Sadílek, Tomáš; Vysoká škola ekonomická v Praze. Fakulta mezinárodních vztahů (2025)
This paper examines the challenges, success factors and success metrics of standardising Early Career Talent Management (ECTM) within multinational corporations (MNCs). In today’s rapidly evolving labour market, investing in junior talent has become increasingly important as industries often require specialised skills that traditional education cannot provide, forcing companies to develop these skills internally. Despite the importance, ECTM is frequently operated through unstructured, locally managed processes. By examining Edwards Lifesciences’ ECTM through expert interviews, this study identifies common challenges in standardisation and highlights the importance of adopting a unified early career framework and terminology. Additionally, it explores key success factors, such as cross-functional collaboration and endorsement of senior leadership. Lastly, the study discusses effective methods for measuring ECTM success, including participants’ feedback and metrics like “time-to-productivity”. This thesis aims to offer actionable recommendations for building a scalable and effective ECTM foundation within MNCs.
Vedoucí práce: Tomáš Sadílek
Bakalářská práce (Bc.)—Vysoká škola ekonomická v Praze. Fakulta mezinárodních vztahů, 2025
Obsahuje bibliografii
Textový (vysokoškolská kvalifikační práce)
Rok obhajoby 2025
Způsob přístupu: Internet
Keywords: international business [obor bakal. práce]; bakalářské práce; bachelor's theses